Konsumsi Sayur dan Buah pada Siswa SMP sebagai Implementasi Pedoman Gizi Seimbang - Fitriyah Nafsiyah Muthmainah; Ali Khomsan; Hadi Riyadi; Guntari Prasetya (Media Kesehatan Masyarakat Indonesia, 2019)
Indonesia is faced with two nutritional problems, namely malnutrition and over nutrition while nutritionalproblems in adolescents tend to be more dominant for being overweight, this can be seen from the prevalenceof adolescent obesity in Cianjur district is 10.6%. Therefore consumption of vegetables and fruits is highlyrecommended to reduce the prevalence of overweight especially in adolescents. The government through theIndonesian Indonesian Balanced-Nutrition Guidelines (PGS) recommends consumption of vegetables and fruitsof 400 g per person per day consisting of 250 g of vegetables and 150 g of fruit. The purpose of this study wasto identify the availability of vegetables and fruits at home, the contribution of vegetables and fruit to vitamin,mineral and fiber intake and the relationship between the nutritional practices of students and mothers as parentsrelated to Indonesian Balanced-Nutrition Guidelines with the consumption of vegetables and fruit. This study wasa cross-sectional study funded by the Neys-van Hoogstraten Foundation, the Netherlands and conducted at SMPN1 Cianjur with a total of 72 students. Data were analyzed using Mann Whitney difference test and Rank Spearmanrelationship test. This research was funded by Neys-van Hoogstraten Foundation, the Netherlands. The amountof fruit and vegetable consumption of students has not been in accordance with Indonesian Balanced-NutritionGuidelines recommendations. The average of vegetable consumption of students was 36.9 ± 34.8 grams per day,while the average of fruit consumption of student was 203.2 ± 112.9 grams per day. There was a significantrelationship (p <0.05) between maternal nutritional practices and nutritional practices of students related to PGSwith consumption of vegetables and fruit of students. This study shows that the consumption of vegetables andfruit in students has not been implemented in accordance with the recommendations of PGS therefore it’s need tomake encouragement to parents which can motivate and familiarize students to consume vegetables and fruit athome